Toward a bioengineered heparin: Challenges and strategies for metabolic engineering of mammalian cells - Baik, Jong Youn (Landes Bioscience, 2012)
Heparin is the most widely used pharmaceutical to control blood coagulation in modern medicine. A health crisis that took place in 2008 led to a demand for production of heparin from non-animal sources. Since Chinese hamster ovary (CHO) cells are capable of producing heparan sulfate (HS), a related polysaccharide naturally, and heparin and HS share the same biosynthetic pathway, we hypothesized that heparin could be produced in CHO cells by metabolic engineering. We developed stable human N-deacetylase/N-sulfotransferase (NDST2) and mouse heparan sulfate 3-O-sulfotransferase 1 (Hs3st1) expressing cell lines based on the expression of endogenous enzymes in the HS/heparin pathways of CHO-S cells. Both activity assay and disaccharide analysis showed that engineered HS attained heparin-like characteristics but not identical to pharmaceutical heparin, suggesting that further balancing the expression of transgenes with the expression levels of endogenous enzymes involved in HS/heparin biosynthesis might be necessary.